A Study of Guidelines for the Management of Health Tourism According to the Perceptions Behaviors of Stakeholders in Nakhornratchasima Province - Klinmuenwai, Kittisak; Eurvongkul, Ratklao (Journal of Applied Economics and Management Strategy, 2023)
This research aims to (1) study and analyze the components of wellness tourism, (2) evaluate the needs in terms of the behaviors and the perceptions in the wellness tourism, (3) search for potential in management and ways to promote and improve the wellness tourism according to the behaviors and the perceptions of people in Nakhon Ratchasima province. This research is mixed methods research, a quantitative data collection method by using a convenient sampling with a group of 485 Thai tourists who visited Nakhon Ratchasima Province, and using a purposive sampling with a group of 16 people of specific respondents who were specialists in tourism from both government and private sectors, community leaders, academics, entrepreneurs, local philosophers and Thai tourists. The study showed that 1) The variation measurement model of the wellness tourism’s components was consistent with the empirical data (χ2= 4.731, df = 3, p-value=0.192, GFI=0.997, AGFI=0.983, CFI=0.999, RMR=0.004, RMSEA=0.033) 2) By prioritizing the needs assessment, in accordance with the behaviors and the receptions in the wellness tourism, with the updated Priority Needs Index method, it revealed that the most essential need was the component No.3 which was the tourist activities at the tourist attractions. 3) By using SWOT analysis in order to search for potential, strengths, weaknesses, opportunities, and obstacles in wellness tourism management and development guidelines according to the behaviors and the perceptions of the concerned people in Nakhon Ratchasima Province, the strength of the tourism components were the attraction and guidelines to improve the wellness tourism, should develop access to tourist attractions, develop and promote diverse tourism activities and develop various tourism facilities to meet the higher standard.